Letter (copy) : Appeal for clothing for Spanish refugees - Tewson, Vincent
032-0064-001 Secretary's. HVT/FC/445. Sch/H/T. 20th April, 1939. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Schevenels, APPEAL FOR CLOTHING FOR SPANISH REFUGEES. I am in receipt of your communication of the 13th instant regarding the appeal for clothing for Spanish Refugees. This is receiving attention and I will write to you again on this matter during the course of next week. Yours sincerely, Assistant Secretary. 292/946/32/64